1968
DOI: 10.1111/j.1432-1033.1968.tb00225.x
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Subunit Structure and Temperature-Sensitivity of Mutant Phenylalanyl RNA Synthetases of Escherichia coli

Abstract: Four independent temperature-sensitive phenylalanyl RNA synthetase mutants of Escherichia co2i differ from the wild type in that cell-free extracts contain phenylalanyl RNA synthetase cross-reacting material exclusively of about half the sue of the wild type enzyme. It therefore seems probable that dissociation or at least weakening of subunit interactions might be the cause of the thermolability of the mutant enzymes.Further evidence supporting this assumption comes from the fact that the wild type enzyme can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
18
0

Year Published

1969
1969
1992
1992

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…An aliquot of this preparation, subjected to acrylamide gel electrophoresis in the presence of sodium dodecyl sulfate and 2-mercaptoethanol (10), gave only one major stained band; this band was located at the place expected of the individual polypeptide chains that comprise Phe-tRNA synthetase (11), and included about 70% of the total material.…”
Section: Resultsmentioning
confidence: 99%
“…An aliquot of this preparation, subjected to acrylamide gel electrophoresis in the presence of sodium dodecyl sulfate and 2-mercaptoethanol (10), gave only one major stained band; this band was located at the place expected of the individual polypeptide chains that comprise Phe-tRNA synthetase (11), and included about 70% of the total material.…”
Section: Resultsmentioning
confidence: 99%
“…Volume of cell suspension was 1.0 ml. the mutant cnzymcs consisted of two, noncatalytic subunits, each half the size of the wild synthetase (Bock 1968). Bock (1968) suggested that the dissociation or weakening of subunit interactions causes the thermolability of this enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…the mutant cnzymcs consisted of two, noncatalytic subunits, each half the size of the wild synthetase (Bock 1968). Bock (1968) suggested that the dissociation or weakening of subunit interactions causes the thermolability of this enzyme. In view of the previously discussed examples of the specific rcquiremcnt for Na+ (Goldman et al 1963;MacLcod 1965) and of the salt activation of cnzymcs from halophilic organisms (Drapeau andMacLeod 1963, 1965;Rhodes and Payne 1966), it seems possible that thermally induced changes in structural and functional areas of synthctasc enzymes or t-RNA molccules may be protected by the binding of Na-' ions to these molcculcs.…”
Section: Resultsmentioning
confidence: 99%
“…Mutations rendering the enzyme temperature-sensitive [4] completely abolish enzyme activity and it has been demonstrated that this inactivation is accompanied by a change in the quaternary structure [5]. Experiments on dissociation of the native enzyme also did not reveal enzyme activity associated with any enzyme form except the 181 000 molecular-weight state [6].…”
mentioning
confidence: 99%